2009
DOI: 10.1007/s10433-009-0116-x
|View full text |Cite
|
Sign up to set email alerts
|

Age effects in prospective memory performance within older adults: the paradoxical impact of implementation intentions

Abstract: This study investigated age effects in prospective memory performance within older adults. The first aim was to explore this issue by examining event-and timebased prospective memory performance in two age groups: young-old (60-75 years) and old-old adults (76-90 years). Moreover, this study for the first time investigated whether forming implementation intentions could be used to improve prospective memory in young-old and old-old adults. Results showed a general effect of age in prospective memory performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 48 publications
(65 reference statements)
5
52
1
1
Order By: Relevance
“…Participants who formed implementation intentions wrote the day of the week twice as often on the response sheets than participants who used alternative memory strategies. Schnitzspahn and Kliegel (2009) confirmed and extended this finding by showing positive implementation intention effects on different types of labbased prospective memory tasks in (young-) old adults. Zimmermann and Meier (2010) could show that the prospective memory performance benefit after forming implementation intentions in older adults was mainly due to a better performance in the prospective component and did not lead to impaired ongoing task performance.…”
Section: Prospective Memory and Implementation Intentionssupporting
confidence: 71%
See 2 more Smart Citations
“…Participants who formed implementation intentions wrote the day of the week twice as often on the response sheets than participants who used alternative memory strategies. Schnitzspahn and Kliegel (2009) confirmed and extended this finding by showing positive implementation intention effects on different types of labbased prospective memory tasks in (young-) old adults. Zimmermann and Meier (2010) could show that the prospective memory performance benefit after forming implementation intentions in older adults was mainly due to a better performance in the prospective component and did not lead to impaired ongoing task performance.…”
Section: Prospective Memory and Implementation Intentionssupporting
confidence: 71%
“…''), which was written down on the worksheet too. Afterward, with eyes closed, participants should mentally imagine and visualize the exact moment and place of the measurement and how they would carry out the blood pressure test (see Liu and Park 2004;Schnitzspahn and Kliegel 2009, for similar procedures). Participants in the control condition were asked to write down the specific times they wanted to perform the blood pressure tests on a worksheet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies applying implementation intentions have augmented the verbal ifthen statement with an imaging component by asking participants to imagine how they will perform the PM task later in the experiment (Kardiasmenos, Clawson, Wilken, & Wallin, 2008;McDaniel et al, 2008;McDaniel & Scullin, 2010;Schnitzspahn & Kliegel, 2009). For instance, Chasteen et al (2001) reported that older adults who were asked to form an implementation intention and then imagine themselves executing the intended action performed better than those who only rehearsed the instructions.…”
mentioning
confidence: 99%
“…Aunque existen numerosos dispositivos artificiales que nos pueden avisar cuáles son las actividades que debemos hacer en el futuro, uno de los retos de la futura investigación en MP será diseñar metodologías que permitan un uso estratégico más eficiente de los recursos intelectuales para realizar estas actividades programadas en el pasado. Pese a las dificultades encontradas en algunos estudios a la hora de mejorar el recuerdo prospectivo en personas mayores o muy mayores (Schnitzspahn, & Kliegel, 2009;McDaniel & Scullin, 2010), es posible mejorar las funciones cognitivas en personas con deterioro debido a la edad (Menacho, 2008). Y este hecho es de especial relevancia si tenemos en cuenta que este deterioro implí-cito puede ser inicio del desarrollo de algunas formas de demencia a medio plazo (Dechamps, Onifade, Decamps, & Bourdel-Marchasson, 2009).…”
Section: Discussionunclassified